Erbium-activated HfO2-based waveguides for photonics - Gonçalves, Rogeria R.; Carturan, Giovanni; Montagna, Maurizio; Ferrari, Maurizio; Zampedri, Luca; Pelli, Stefano; Righini, Giancarlo C.; Ribeiro, Sidney J.L. [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 2004)
Silica-based sol-gel waveguides activated by Er3+ ions are attractive materials for integrated optic devices. 70SiO(2)-30HfO(2) planar waveguides, doped with Er3+ concentrations ranging from 0.01 to 4 mol%, were prepared by sol-get route. The films were deposited on v-SiO2 and silica-on-silicon substrates, using dip-coating technique. The waveguides show a homogeneous surface morphology, high densification degree and uniform refractive index across the thickness. Emission in the C-telecommunication band was observed at room temperature for ill the samples upon excitation at 980 nm. The shape is found to be almost independent on erbium content, with a FWHM between 44 and 48 nm. The I-4(13/2) level decay curves presented a single-exponential profile, with a lifetime ranging between 1.1 and 6.7 ms, depending on the erbium concentration. The waveguide deposited on silica-on-silicon substrate supports one single propagation mode at 1.5 mum with a confinement coefficient of 0.85, and a losses of about 0.8 dB/cm at 632.8 nm. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: optical materials; planar waveguides; erbium; silica-hafnia; sol-gel; silica-on-silicon